Activated sludge reaction and solid-liquid separation equipment - JI JUNJIE; XU TING; WU JUN; JIANG XINYUE; YU LINTANG (2015)
The utility model discloses an activated sludge reaction and solid-liquid separation equipment belongs to the water treatment facilities field. An activated sludge reaction and solid-liquid separation equipment, is including the aerobic reaction that is linked together district (1), settling zone (3), be equipped with aeration equipment (6) in the aerobic reaction district (1), characterized by, be equipped with between aerobic reaction district (1), settling zone (3) settling zone baffle (11), settling zone baffle (11) below is muddy water passageway (7), and aerobic reaction district (1), settling zone (3) are linked together through muddy water passageway (7), settling zone bottom plate (12) slope sets up, and settling zone bottom plate (12) least significant end setting is in the bottom of muddy water passageway (7). The utility model discloses when improving the sewage treatment effect and ensureing out the water effect, reduce disposable input and reduce the running cost, reduce structures area, the operation management of being convenient for.